"STRESSED OUT": The role of FUS and TDP-43 in amyotrophic lateral sclerosis. (September 2020) - Aksoy, Yagiz Alp; Deng, Wei; Stoddart, Jack; Chung, Roger; Guillemin, Gilles; Cole, Nicholas James; Neely, Graham Gregory; Hesselson, Daniel
Abstract: Mutations in fused-in-sarcoma (FUS) and TAR DNA binding protein-43 (TDP-43; TARDBP) are known to cause the severe adult-onset neurodegenerative disorder amyotrophic lateral sclerosis (ALS). Proteinopathy caused by cellular stresses such as endoplasmic reticulum (ER) stress, oxidative stress, mitochondrial stress and proteasomal stress and the formation of stress granules (SGs), cytoplasmic aggregates and inclusions is a hallmark of ALS. FUS and TDP-43, which are DNA/RNA binding proteins that regulate transcription, RNA homeostasis and protein translation are implicated in ALS proteinopathy. Disease-causing mutations in FUS and TDP-43 cause sequestration of these proteins and their interacting partners in the cytoplasm, which leads to aggregation. This mislocalization and formation of aggregates and SGs is cytotoxic and a contributor to neuronal death. We explore how loss-of-nuclear-function and gain-of-cytoplasmic function mechanisms that affect FUS and TPD-43 localization can generate a 'stressed out' neuronal pathology and proteinopathy that drives ALS progression.